SIKAP REMAJA MASJID TERHADAP NORMA KELlJARGA KECIL - Subardhi, Subardhi (Jurnal Cakrawala Pendidikan, 2016)
This investigation was designed to examine the relationship that exist among Mosque youngster's knowledge of Islam, Mosque youngster's knowledge of population problem and Mosque youngster's attitude toward small family norm. This relationship would be studied in corellational form by independently or collectively. The subject of this research was the Mosque youngster's at Surabaya. This research used a survey method. The sample included 210 persons. The data were collected using simple and multiple regression analysis. The finding of this research were, first, a positive highly significant correlation existed between mosque youngster's knowledge of Islam and mosque youngster's attitude toward small family norm. Second, a positive highly significant correlation existed between mosque youngster's knowledge of population problems and mosque youngster's attitude toward small family norm. Third, a positive highly significant multiple correlation existed among mosque youngster's knowledge of Islam and mosque youngster's knowledge of population problem collectively and mosque youngster's attitude toward small family norm.